Transformation of Indonesia's Trade Policy on Nickel Commodities - Sudiana, Dimas Ramdhan Sudiana; Dermawan, Windy; Lanti, Irman Gumilang (Yayasan Ilomata, 2025)
This article examines the direction and dynamics of Indonesia's trade policy on nickel commodities since 2020, particularly after the implementation of the nickel ore export ban. Indonesia's transformation from a major raw nickel ore exporter to the world's leading supplier of processed nickel products represents a striking example of how industrial policy can drive economic transformation in resource-rich countries. This policy not only signaled a shift in the management of natural resources but also triggered reactions from global actors, including a formal lawsuit by the European Union through the WTO's dispute settlement mechanism. Using a qualitative approach and comprehensive literature review, this article aims to explain how the nickel downstreaming policy has been positioned as a strategic instrument to achieve national interests in the global economy. The research demonstrates that Indonesia's assertive trade policy has tested the boundaries of the international trading system, reflecting broader trends of resource nationalism among developing countries seeking greater control over their natural resources. By analyzing official documents, government statements, and extensive academic studies, this article highlights the relationship between economic nationalism, international trade dynamics, and the challenges facing developing countries in asserting resource sovereignty. The findings demonstrate that while downstreaming boosts macro-economic metrics and strengthens Indonesia's position in global value chains, it creates significant distributional, environmental, and geopolitical challenges that require careful policy refinement to balance economic nationalism with sustainability and international trade obligations.